2023
DOI: 10.1186/s13048-023-01162-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n-3 PUFA supplementation on oocyte in vitro maturation in mice with polycystic ovary syndrome

Abstract: Abstractn-3 PUFAs are classic antioxidant that can be used to treat follicular dysplasia and hyperinsulinemia caused by excessive oxidative stress in PCOS women. To investigate the effect of n-3 PUFA supplementation on the oocyte quality of polycystic ovary syndrome (PCOS) mice during in vitro maturation, a PCOS mouse model was established by dehydroepiandrosterone (DHEA). The GV oocytes of the control and PCOS groups were collected and cultured in vitro with or without n-3 PUFAs. After 14 h, the oocytes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Three-week-old C57BL/6 mice were randomly divided into 2 groups ( n = 18 for each group) and were injected with dehydroisoandrosterone (DHEA, Macklin, Shanghai, China)(6 mg/100 g body weight) and sesame oil (Macklin, Shanghai, China) for 21 consecutive days respectively as described previously [ 66 ]. All mice were anesthetized with 3% isoflurane (ISO) (in 40% oxygen) and were euthanized by bloodletting prior to dissection at preset time intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Three-week-old C57BL/6 mice were randomly divided into 2 groups ( n = 18 for each group) and were injected with dehydroisoandrosterone (DHEA, Macklin, Shanghai, China)(6 mg/100 g body weight) and sesame oil (Macklin, Shanghai, China) for 21 consecutive days respectively as described previously [ 66 ]. All mice were anesthetized with 3% isoflurane (ISO) (in 40% oxygen) and were euthanized by bloodletting prior to dissection at preset time intervals.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to highlight that different types of PUFAs affect oocyte quality differently. ω3-PUFAs can decrease abnormal oxidative stress levels and spindle/chromosome aberration rates in oocytes [103]. The consumption of long-chain ω3-PUFAs safeguards reproductive function and is linked to a greater likelihood of successful reproduction in women undergoing assisted reproduction [104,105].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Alam et al proposed that SIRT1 may prevent cell dysfunction by reducing oxidative stress-induced cell damage [21]. In recent years, there have been increasing studies on the role of SIRT1 in anti-oxidative stress [21][22][23], but few studies have investigated its antioxidant effect in premature ovarian failure (POF). It has been reported that the activation of AMPK can activate SIRT1 (histone deacetylase 1) [24], additionally, PPAR-γ (peroxisome proliferator-activated receptor γ) has been reported to act as a transcription factor that inhibits SIRT1 gene expression, and the expression of PPAR-γ is inhibited by AMPK [25,26].…”
Section: / 34mentioning
confidence: 99%